Dynamic Response Law of Loess Slope with Different Shapes. (25th March 2019) - Yan, Zhixin; Zhang, Sen; Zhang, Xuedong; Jiang, Ping
Abstract : Loess slope broadly distributes in Northwest China, making the slope of the area developed. And with the development number of construction projects still on the rise, this area is a high-intensity region with multiple earthquakes, resulting in landslide under earthquakes which is a very serious problem. However, the study on the loess slope dynamic response yet rarely involved the exploration of the influence of slope shapes, which leaves a hidden danger to the safety of local engineering. In this paper, a typical ladder-type loess slope in engineering is selected as a research object, and a numerical simulation model is established with FLAC3D program. The dynamic response of the loess slope with different shapes is studied deeply and systematically. Found a series phenomenon of earthquake response of loess slope with stepped slope series, the width of the platform and the slope ratio change under earthquakes. Meanwhile, the law of slope parameters such as slope series, platform width, and slope ratio on dynamic response of loess slope is revealed. The results provide theoretical support and scientific basis for the construction of the relevant projects in the area, which has important reference value to the safety of the engineering and the development of economic society.